Effets circulatoires et respiratoires de la kétamine chez le cheval anesthésié à l'halothane. - Serteyn, D (1987)
Ketamine (0.3 mg/kg) administered intravenously to 12 halothane anesthetized horses caused a significant respiratory depression during ten minutes when respiration was spontaneous. Significant hemodynamic effects were not observed except for cardiac index. Clinical application was also discussed.